If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20z + 3z + -21z + -1 = 13 Reorder the terms: -1 + 20z + 3z + -21z = 13 Combine like terms: 20z + 3z = 23z -1 + 23z + -21z = 13 Combine like terms: 23z + -21z = 2z -1 + 2z = 13 Solving -1 + 2z = 13 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2z = 13 + 1 Combine like terms: -1 + 1 = 0 0 + 2z = 13 + 1 2z = 13 + 1 Combine like terms: 13 + 1 = 14 2z = 14 Divide each side by '2'. z = 7 Simplifying z = 7
| -78=6U+12 | | 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) | | 50+5x=15+12x | | 12x-5=4x-1 | | 7x+11=7+7x | | -2(-4+y)-5y=15 | | -13+4b=-3b-7 | | 4x-3+2x+53=90 | | y=5x^2+2x-1 | | -3(g-9)+-9=-9 | | 4x-3+2x+53=180 | | 3x+x-2=-x+7 |